Effect of over-the-counter whitening products associated or not with 10% carbamide peroxide on color change and microhardness: In vitro study - Jurema, Ana L.B. [UNESP]; Claudino, Evaniele S. [UNESP]; Torres, Carlos R.G. [UNESP]; Bresciani, Eduardo [UNESP]; Caneppele, Taciana M.F. [UNESP] (Jaypee Brothers Medical Publishing, 2018)
Aim: The purpose of this in vitro study was to evaluate the color and microhardness of teeth subjected to different overthe- counter (OTC) whitening products in association or not with 10% carbamide peroxide (10% CP). Materials and methods: Enamel-dentin specimens (n = 210) were obtained from bovine incisors and stained. Half of the specimens were then subjected to daily cycles of staining (5 minutes), 10% CP bleaching (8 hours) in association with OTC products, and artificial saliva storage until complete 24 hours, for 2 weeks; the other half was subjected to daily cycles of staining, OTC treatment, and storage in artificial saliva for 12 weeks. The specimens were divided into 14 groups according to the OTC: CP-Water and Water (deionized water); CP-Listerine and Listerine (whitening mouth rinse); CP-Brushing and Brushing (mechanical brushing); CP-Colgate and Colgate (conventional toothpaste), CP-ColgateW and ColgateW, CP-OralBW and OralBW, and CP-CloseUpW and CloseUpW (whitening toothpaste). After staining and whitening, color and microhardness were measured. Data were submitted to analysis of variance (ANOVA) and the Tukey's test for multiple comparisons for color analysis and the paired t-test for microhardness analysis. Results: The CP and CloseUpW groups had the largest color change (ΔE00). The teeth treated with Colgate increased significantly in microhardness after whitening. Conclusion: The association of 10% CP with OTC whitening agents did not increase the whitening effect or microhardness. The OTC agents containing hydrogen peroxide and abrasives had a similar effect to one another but were not as effective as the CP groups and the subgroup brushed only with blue covarine toothpaste. Clinical significance: The current study provides information about the mechanism of OTC whitening products. None of the whitening agents evaluated damaged the enamel when used according to the manufacturers' instructions. The use of toothpaste containing hydrogen peroxide or abrasives cannot provide a whitening effect similar to at-home bleaching, and this does not improve with the association with 10% CP. However, toothpaste containing blue covarine has a satisfactory whitening effect immediately after brushing.
Keywords: Laboratory research; Mouthwashes; Tooth bleaching; Toothpaste